Why Women Have Lower Retirement Savings: The Australian Case. Issue 1 (2nd January 2019) - Feng, Jun; Gerrans, Paul; Moulang, Carly; Whiteside, Noel; Strydom, Maria
Abstract : This study provides empirical evidence of the gender gap in retirement savings trajectories using a large longitudinal Australian database. The persistent trend of retirement income policy over recent decades has been to place responsibility for retirement savings accumulation with the individual employee. These plans are fundamentally linked to employment conditions and individual choices, which shape retirement savings trajectories and outcomes. Australia has a mature compulsory system and thus provides insight for countries embarking on similar paths. This study shows that the gender gap in retirement savings is observable from early on in an individual's paid working life and persists over time, providing evidence that women are disadvantaged early in their careers, with few signs of improvement. Men, in contrast, are overrepresented in the upper quartile of growth in retirement savings. This study provides important empirical evidence for policymakers concerned with gender differences in retirement outcomes.